An Analysis of Jakarta's Democracy and Political Power in 2019 - Pureklolon, Thomas Tokan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Indonesia is a democratic country striving to realize people's sovereignty in the government. Indonesia consists of 34 provinces, one of which is Jakarta. This research aimed to analyze the democracy and political power in Jakarta in 2019 by employing the literature review. The researchers had collected the data from primary and secondary sources found in the articles and the web, which were then analyzed using a descriptive qualitative approach. The results show that democracy and political power are closely related. In political practice, democracy exists as an instrument to gain power. The aspect of democracy in gaining political power has been well implemented in the political, social, and cultural factors. Besides, the Indonesian democracy index reveals that Jakarta ranks first in Indonesia. Jakarta already has an exemplary democracy, but it still needs to continue to evaluate each indicator to defend its ranking.